Body by science : a research based program for strength training, body building, and complete fitness in 12 minutes a week - McGuff, Doug.; Little, John R., 1960- (New York : McGraw-Hill, 2009)
Explains the role of exercise in health, and suggests a workout routine that emphasizes high-intensity, low-frequency weight training, and de-emphasizes more traditional aerobic-centered exercise.
Whom can you trust? -- Defining "health, fitness, and exercise" -- Global betabolic conditioning -- The dosoe-response relationship of exercise -- The big-five workout -- The benefits of the big-five workout -- Enhancing the body's response to exercise -- Tweaking the exercise stimulus -- The genetic factor -- The science of fat loss -- The ideal training programs for athletes -- ... for seniors -- The scientific literature supporting Body by Science.
Includes bibliographical references (pages 249-275) and index.
Keywords: Exercise; Physical fitness; Weight loss; Bodybuilding -- Physiological aspects